Pengembangan pedoman handover di ruang rawat inap rumah sakit Universitas Indonesia - Magdalena, Helen; Handiyani, Hanny; Pujasari, Hening; Hariyati, Roro Tutik Sri; Sari, Erna Puspita (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The handover process in nursing care is very important because it is directly related to patient safety and continuity of care. A suboptimal handover can increase the risk of medical errors. Purpose: To develop handover guidelines in the inpatient ward of the University of Indonesia Hospital. Method: A case report study on the preparation of handover guidelines was conducted at the University of Indonesia Hospital on September 2 - October 2, 2024. This activity includes assessment, data analysis, action plan (Plan of Action/PoA), implementation, and evaluation. Data collection was carried out through interviews, observations, and questionnaires. The approach used to solve the problem through Kurt Lewin's theory of change. Results: Shows that the implementation of handover is not optimal with variations in methods used, including conferences and handovers at the bedside. The results of the study indicate that the implementation of the handover SOP has not been consistently adhered to by ward nurses and several factors such as time constraints and lack of supervision have a negative effect on the effectiveness of the handover. Conclusion: The implementation of handovers in inpatient rooms has not been optimal due to inconsistencies in the application of SOPs, time constraints, and lack of supervision. The development of handover guidelines with the Kurt Lewin change theory approach is a strategic step to improve the effectiveness and consistency of handovers. Wider dissemination of guidelines and regular monitoring are needed to ensure patient safety and the quality of sustainable nursing care. Suggestion: Handover guidelines need to be updated regularly based on scientific evidence (evidence-based practice) to remain relevant to developments in nursing science. Socialization and implementation activities of handover conferences and handovers at the patient's bedside need to be monitored and evaluated routinely to ensure their effectiveness in improving the quality of patient handovers. Keywords: Handover; Guidelines; Development; Inpatient; Hospital. Pendahuluan: Proses serah terima atau handover dalam asuhan keperawatan sangat penting karena secara langsung berhubungan dengan keselamatan pasien dan kontinuitas perawatan. Handover yang tidak optimal dapat meningkatkan risiko kesalahan medis. Tujuan: Untuk mengembangkan pedoman handover di ruang rawat inap rumah sakit Universitas Indonesia. Metode: Penelitian case report mengenai pengembangan panduan handover, dilakukan di Rumah Sakit Universitas Indonesia pada 2 September – 2 Oktober 2024. Kegiatan ini meliputi pengkajian, analisis data, rencana tindakan plan of action (PoA), implementasi, dan evaluasi. Data dikumpulkan melalui wawancara, observasi, dan pengisian kuesioner. Pendekatan yang digunakan untuk menyelesaikan masalah melalui teori perubahan Kurt Lewin. Hasil: Menunjukkan bahwa pelaksanaan handover belum optimal dengan variasi metode yang digunakan, termasuk conference dan bedside handover. Hasil menunjukan bahwa pelaksanaan SPO handover tidak konsisten dipatuhi perawat ruangan dan beberapa faktor, seperti keterbatasan waktu dan kurangnya supervisi berpengaruh negatif terhadap efektivitas handover. Simpulan: Pelaksanaan handover di ruang rawat inap belum berjalan secara optimal akibat ketidakkonsistenan dalam penerapan SPO, keterbatasan waktu, dan kurangnya supervisi. Pengembangan panduan handover dengan pendekatan teori perubahan Kurt Lewin menjadi langkah strategis untuk meningkatkan efektivitas dan konsistensi handover. Sosialisasi panduan yang lebih luas dan monitoring berkala diperlukan untuk menjamin keselamatan pasien dan kualitas asuhan keperawatan yang berkelanjutan. Saran: Panduan handover perlu diperbarui secara berkala berdasarkan bukti ilmiah (evidence-based practice) agar tetap relevan dengan perkembangan ilmu keperawatan. Kegiatan sosialisasi dan implementasi handover conference serta bedside handover perlu dimonitoring dan dievaluasi secara rutin untuk memastikan efektivitasnya dalam meningkatkan kualitas serah terima pasien. Kata Kunci: Handover; Pedoman; Pengembangan; Rawat Inap; Rumah Sakit.